Integration Policy Towards Immigrants: Current Experience - Nadiia Bureiko (CES Working Papers, 2012)
In the contemporary world the intensity of the immigration movements is constantly increasing. Countries which experience great immigrant flows are facing numerous problems which should be solved. The article studies the current immigration flows in EU countries, the United States of America and Canada and presents three main models of integration policy towards immigrants – political assimilation, functional integration and multicultural model. Separate models are distinguished for the Muslims' integration. The author examines the peculiarities of every model and examines the conclusions provided by the Migrant Integration Policy Index (MIPEX) concerning the situation of the immigrants' integration in 31 countries in 2011. Among all the policy indicators the first that are defined are as follows: political participation, education, labour market mobility and anti-discrimination. The situation with immigrants' integration in Ukraine is also studied as it is gaining a great attention of the authorities and the public. The measures and practical steps done regarding this situation in Ukraine in recent years are analyzed using the information offered by the State Migration Service of Ukraine.
Keywords: J15; J61; J62; O15; F22; 330; immigration; immigrants flows; integration policy; aliens; ethnic identity; society; citizenship Romania